Kreativität im Musikunterricht in Zeiten von Kompetenzorientierung. Entwicklung eines Modells kreativer Kompetenz in Musik - Hasselhorn, Johannes (43. Jahresband des Arbeitskreises Musikpädagogische Forschung, 2022)
Creativity is an important goal dimension of learning in school in general and of music education in particular. Despite a multitude of theoretical considerations, no valid and reliable measurement instrument for music-related creativity is available until today. Against the background of competence orientation, this paper there- fore attempts to create a model of creative competence in music. For this purpose, considerations of Amabile and Webster are combined to a competence model with three dimensions and six subdimensions. The model differentiates between creative thinking processes, music-speciϔic knowledge and expertise, and motivational pre- requisites. Implications of this proposed model are discusse